Eupafolin and Ethyl Acetate Fraction of Kalanchoe gracilis Stem Extract Show Potent Antiviral Activities against Enterovirus 71 and Coxsackievirus A16. (2nd September 2013) - Wang, Ching-Ying; Huang, Shun-Chueh; Lai, Zhen-Rung; Ho, Yu-Ling; Jou, Yu-Jen; Kung, Szu-Hao; Zhang, Yongjun; Chang, Yuan-Shiun; Lin, Cheng-Wen
Abstract : Enterovirus 71 (EV71) and coxsackievirus A16 (CoxA16) are main pathogens of hand-foot-and-mouth disease, occasionally causing aseptic meningitis and encephalitis in tropical and subtropical regions. Kalanchoe gracilis, Da-Huan-Hun, is a Chinese folk medicine for treating pain and inflammation, exhibiting antioxidant and anti-inflammatory activities. Our prior report (2012) cited K. gracilis leaf extract as moderately active against EV71 and CoxA16. This study further rates antienteroviral potential of K. gracilis stem (KGS) extract to identify potent antiviral fractions and components. The extract moderately inhibits viral cytopathicity and virus yield, as well as in vitro replication of EV71 (IC50 = 75.18 μ g/mL) and CoxA16 (IC50 = 81.41 μ g/mL). Ethyl acetate (EA) fraction of KGS extract showed greater antiviral activity than that of n -butanol or aqueous fraction: IC50 values of 4.21 μ g/mL against EV71 and 9.08 μ g/mL against CoxA16. HPLC analysis, UV-Vis absorption spectroscopy, and plaque reduction assay indicate that eupafolin is a vital component of EA fraction showing potent activity against EV71 (IC50 = 1.39 μ M) and CoxA16 (IC50 = 5.24 μ M). Eupafolin specifically lessened virus-induced upregulation of IL-6 and RANTES by inhibiting virus-induced ERK1/2, AP-1, and STAT3 signals. Anti-enteroviral potency of KGS EA fraction and eupafolin shows the clinical potential against EV71 and CoxA16 infection.